Utilization of carrageenan in improving the textural quality of fishfalls - Rosales Perla D.; Gomez, Ma. Theresa L. (1992.)
This study was done to assess the effect of carrageenan on some rheological and water-holding properties of fish balls. In the first phase, the formulation developed by Libunao (1989) was evaluated. The texture was very firm and the general acceptability was neither like nor dislike to like slightly. Four different formulations then were developed. No significant difference was detected among the samples based on the sensory evaluation. The best formulation considered was fish balls with 15.53% cornstarch and 0% emulsion. Carrageenan was incorporated in the fish balls in the second phase. The best type of carrageenan was determined. Iota, kappa and iota-kappa combinations at 0.50% by weight of the total formulation were added separately with the fourth lot serving as the control. Objective tests on WHC, firmness and % weight loss showed no significant difference. Likewise, no significant difference was detected in the sensory evaluation except for firmness. The best product considered was the sample with kappa-iota carrageenan. The texture was moderately firm. Iota-kappa carrageenan was incorporated at 0.25%, 0.50% and 0.75% by weight. Results showed that WHC increased and firmness decreased as the concentration of iota-kappa carrageenan increased. In the sensory evaluation. 0.75% kappa-iota containing sample was judged as the best product with moderate firmness and the general acceptability was like moderately. The formulation of 0.75% kappa-iota containing sample was translated into bench scale production. The cost of 200±10 grams of fish balls from bench scale production was P20.56. With 15% mark-up, the selling price is P23.64.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fishery processing; Chondrus crispus